Melanoma toolkit for early detection for primary care clinicians: a 1-year follow-up on outcomes - Diehl, Kyra; Stoos, Elizabeth; Becker, Alyssa; Orfaly, Victoria E.; Nelson, Jacob; Gillespie, Jordan; Ng, Justin; Tobey, Tayler; Latour, Emile; Ludzik, Joanna; Berry, Elizabeth G.; Geller, Alan C.; et al. (Frontiers in Medicine, 2024)
Introduction: Primary care providers or clinicians (PCPs) have the potential to assist dermatologists in screening patients at risk for skin cancer, but require training to appropriately identify higher-risk patients, perform skin checks, recognize and biopsy concerning lesions, interpret pathology results, document the exam, and bill for the service. Very few validated dermatology training programs exist for PCPs and those that are available focus primarily on one emphasis area, which results in variable efficacy and single-topic limited scope. Methods: We have created a free, online, continuing education program (Melanoma Toolkit for Early Detection, MTED) that allows learners to choose from a variety of multimedia tools (image recognition, videos, written material, in-person seminars, self-tests, etc.) that suits their learning style and time availability. Here we present the toolkit, the development and validation of the curriculum, and report on one-year outcomes of a nested survey study. Because the goal of the program is to maximize participation by allowing PCPs to tailor their experience to their own needs and interests, the majority of participants did not complete every element of the program. Results: A total of 8,683 PCPs have accessed at least one element of the toolkit from 2019-2024. Participants completed a pre-survey, online training module, and post-survey that included selfreported screening behaviors, changes in confidence, and malignant and benign lesion categorization based on clinical images. A total of 139 pre-surveys and 92 post-surveys were completed, including 55 matched participants that completed both the pre-and post-training surveys. There were significant improvements in PCP confidence (P < 0.001) and malignant (P < 0.001) and benign image (P = 0.029) identification respectively. Discussion: PCPs may serve as a valuable aid in skin cancer screening efforts, but additional studies are needed to evaluate the impact of these curricula in clinical practice.